Monte Carlo Modeling of DNA Lesions and Chromosomal Aberrations Induced by Mixed Beams of Alpha Particles and X-Rays - Brzozowska, Beata; Tartas, Adrianna; Wojcik, Andrzej (Frontiers in Physics, 2020)
Prediction of health risks associated with exposure to mixed beams of high and low LET (linear energy transfer) ionizing radiation is based on the assumption that the biological effect caused by them equals the sum of effects resulting from the action of individual beam components. Experimental studies have been published indicating that the cellular effects in cells exposed to mixed radiations are higher than calculated based on the assumption of additivity. The present work contains a comparative analysis of published results on chromosomal aberrations in human peripheral blood lymphocytes exposed to mixed beams of alpha particles and X-rays with computer simulations using the PARTRAC program based on Monte Carlo methods. PARTRAC was used to calculate the levels of DNA single-strand breaks (SSB) and double-strand breaks (DSB - both complex and simple) and of chromosomal aberrations. The levels and SSB and DSB were found to be additive. A synergistic effect was obtained at the level of chromosomal aberrations, being in good agreement with the experimental results. This result demonstrates that the synergistic action of mixed beams results from processing of SSB and DSB, and not from their initial frequencies. The level of synergy was dependent on the composition of the mixed beam, with highest level at a 50:50 ratio of alpha particles and X-rays.